What Determines Informal Economy and Informal Employment - The Case of North Macedonia - Trpeski, Predrag; Trenovski, Borce; Kozheski, Kristijan; Cvetanoska, Marijana (University of Belgrade, Faculty of Economics and Business - Publishing Centre, 2022)
The importance of the informal economy is seen in the fact that more than 60% of world employment operates in some form of informal economy. Additionally, on average, about 35% of GDP in developing countries is generated in the informal sector, while the informal sector in these countries employs about 70% of the workforce. In the case of the Republic of North Macedonia, this proportion ranges from 36% to 24% for the period 2006 - 2021 which confirm the relevance of this research. The aim of the paper is first to estimate the level of informal economy in the country and furthermore to analyze the impact of the main determinants - labor market determinants on the informal production and informal employment in the Republic of North Macedonia. We employ regression analyses for the period 2006-2021 to determine the key factors behind informal economy and informal employment. The following variables are included in the analysis: Labor Freedom, Tax Burden, Business Freedom, Minimum Wage, and Self-Employed workers. The results of the empirical analysis show that the increase in Labor Freedom and Tax Burden has statistically significant impact on informal production growth, while increase in Business Freedom statistically significantly reduces the informal economy. The increase in the proportion of the minimum wage relative to the average wage causes a reduction in informal production. Regarding informal employment, the obtained results show that the growth of Labor Freedom and Business Freedom has statistically significant impact on informal employment. Also, regarding the self-employed, the growth of this category of employment has statistically significant positive impact on the growth of informal employment.
Keywords: DETERMINANTS OF SHADOW ECONOMY, INFORMAL LABOR MARKET, LABOR MARKET INSTITUTIONS, SHADOW ECONOMY.